Arsenic trioxide regulates DYNAP through hsa-mir-573 and inhibits the proliferation of laryngeal cancer - Yanru Ren; Xiao Yang; Yang Hui; Weiyao Chen; Yi Cheng; Ning Zhang; Tao Liu; Xinxin Yang; Xiaoyu Li (Scientific Reports)
Abstract Laryngeal squamous cell carcinoma (LSCC) is a malignant tumor with limited treatment options and poor prognosis in advanced stages. Arsenic trioxide (ATO), a drug well-known for treating acute promyelocytic leukemia, has shown potential antitumor effects in several solid tumors. This study aimed to investigate the role of ATO on LSCC proliferation and its underlying molecular mechanisms. LSCC cell lines (TU212, TU686, and AMC-HN-8) were treated with varying concentrations of ATO, and cell proliferation was evaluated using CCK-8, colony formation, and EdU assays. miRNA-sequencing identified differentially expressed miRNAs after ATO treatment, and bioinformatics tools predicted hsa-miR-573 target genes. The interaction between hsa-miR-573 and dynactin-associated protein (DYNAP) was validated by dual-luciferase reporter assays. Additionally, a xenograft tumor model was established to examine the in vivo effects of ATO on tumor growth. ATO significantly inhibited LSCC cell proliferation in a dose- and time-dependent manner. miRNA-sequencing identified hsa-miR-573 as significantly upregulated following ATO treatment, and functional studies demonstrated that hsa-miR-573 suppresses LSCC cell proliferation by directly targeting DYNAP. Overexpression of DYNAP promoted LSCC cell proliferation, while DYNAP knockdown reversed this effect. In vivo, ATO treatment suppressed tumor growth in nude mice without significant nephrotoxicity or cardiotoxicity. Mechanistically, ATO reduced the expression of DYNAP and inhibited the PI3K/AKT signaling pathway. ATO inhibited LSCC progression by upregulating hsa-miR-573, which directly targets DYNAP to suppress cell proliferation and disrupt the PI3K/AKT signaling pathway. These findings supported the potential of ATO as a therapeutic agent for LSCC.